PROBLEMATIKA LITERASI DIGITAL DI SMP NEGERI 2 PUJUT: ANALISIS KESENJANGAN KOMPETENSI, PEDAGOGI, INFRASTRUKTUR, DAN TATA KELOLA - LL. Herry Anggara, Erick; Roihatul Ilmi; Muhammad Sanusi; Marisa Arni; Basilius Redan Werang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study analyzes digital literacy problems at SMP Negeri 2 Pujut by examining the relationship between students' literacy outcomes, teacher capacity, instructional quality, facilities, and school governance. It employed a descriptive qualitative approach with a document-based case study design. Data were obtained from the 2025 Education Report, the 2026 School Profile, and the 2026 Teacher List. The analysis involved indicator extraction, thematic coding, cross-document triangulation, and interpretation using the five competence areas of DigComp 2.2: information and data literacy, communication and collaboration, digital content creation, safety, and problem solving. The findings show that the proportion of students reaching the minimum literacy competency increased from 33.33% in 2024 to 66.67% in 2025. Nevertheless, 33.33% of students remained below or far below the minimum level. Critical reasoning also remained at a moderate level, with a score of 51.24. Teacher training experience received a score of 0, while all teachers assigned to Informatics and Coding were recorded as having educational backgrounds that were not aligned with the subjects. The information and communication technology facility index reached 100, but the school had no computer laboratory, its multimedia room was moderately damaged, and the room feasibility index was only 22.22. These findings reveal a gap between administratively recorded availability, usable access, pedagogical competence, and direct measurement of digital literacy. Improvement should prioritize digital competency diagnosis, continuous teacher professional development, cross-curricular source evaluation and digital safety tasks, scheduled optimization of available devices, and measurable monitoring indicators.